A rare case of asymptomatic axial rotation of the gravid term uterus by 180 degrees (Indian Journal of Case Reports, 2019)
Some degree rotation of the gravid uterus in pregnancy is not an abnormal finding.However, extreme uterine torsion of 180 degrees around its cervical junction is a relatively rare event in obstetrics. Most women undergoing atorsion present with symptoms. Here, we report a rare case of asymptomatic uterine torsion detected at laparotomy for an emergency cesarean sectiondue to transverse lie in labor. As derotation of the gravid term uterus was not possible, a transverse incision in the lower posterior uterine segment was given. The clinical challenge of uterine torsion lies in its non-specific clinical course and rarity of this condition makes the preoperative diagnosis difficult.